Obstacle-Aware Crowd Surveillance with Mobile Robots in Transportation Stations - Yumin Choi; Hyunbum Kim (Sensors)
Recent transportation systems are operated by cooperative factors including mobile robots, smart vehicles, and intelligent management. It is highly anticipated that the surveillance using mobile robots can be utilized in complex transportation areas where the high accuracy is required. In this paper, we introduce a crowd surveillance system using mobile robots and intelligent vehicles to provide obstacle avoidance in transportation stations with a consideration of different moving strategies of the robots in an existing 2D area supported by line-based barriers and surveillance formations. Then, we formally define a problem that aims to minimize the distance traveled by a mobile robot, while also considering the speed of the mobile robot and avoiding the risk of collisions when the mobile robot moves to specific locations to fulfill crowd surveillance. To solve this problem, we propose two different schemes to provide improved surveillance that can be used even when considering speed. After that, various ideas are gathered to define conditions, set various settings, and modify them to evaluate their performances.